Pedagogical Investigations: Wittgenstein and education - Michael A. Peters (Universidade Federal do Rio Grande do Sul, 2020)
In this brief autobiographical excursus, Professor Michael Peters not only presents us with the most fundamental aspects of his thinking in philosophy of education, but reveals how, in the midst of some specific concerns, his encounter with Wittgenstein and post-structuralist philosophers ended up shaping the way that he traveled in his intellectual path.